Influence of exogenous supplementation of IGF-I, cysteamine and their combination on in vitro caprine blastocyst development - GOEL, PUJA; GOEL, A K; BHATIA, A K; KHARCHE, S D (The Indian Journal of Animal Sciences, 2017)
The present study was carried out to investigate the putative beneficial effects of insulin-like growth factor-I (IGF-I) and cysteamine supplementation alone or their combination on in vitro embryo development competence of fertilized goat oocytes. Presumptive zygotes (18 h post insemination) were randomly assigned for in vitro embryo development in embryo development medium (EDM) supplemented with IGF-I (Gr. 1), Cysteamine (Gr. 2), IGF- I + Cysteamine (Gr. 3) and Control containing only EDM (Gr. 4). Statistically non-significant difference was observed in cleavage rate among all the treated groups. Morula formation rate was significantly higher in IGF-I supplemented group compared to IGF-I + cysteamine supplemented and non-supplemented (control) groups. Furthermore, supplementation of IGF-I, cysteamine and IGF-I + cysteamine in embryo culture medium significantly improved blastocyst formation rate compared to control. However, a nonsignificant difference in blastocyst formation was observed among the supplemented groups. These findings lead to the conclusion that under in vitro conditions, supplementation of IGF-I and cysteamine alone or combination in IVC media were equally effective in embryo development and blastocyst production, however, this effect was significantly higher as compared to non- supplemented group (control).